2019
DOI: 10.21873/cgp.20129
|View full text |Cite
|
Sign up to set email alerts
|

The Association of a Novel Identified VDR SNP With Prostate Cancer in African American Men

Abstract: Background/Aim: Vitamin D receptor (VDR) is present in numerous cellular pathways and it has been suggested that VDR genetic variants influence individual susceptibility to prostate cancer. Also, analyses of single nucleotide polymorphisms (SNPs) in VDR revealed ethnicityassociated polymorphisms. The aim of this study was to identify VDR SNPs in African American men with and without prostate cancer. Materials and Methods: The entire VDR gene was screened for germline mutations in a casecontrol study by denatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
0
9
1
1
Order By: Relevance
“…Moreover, a case-control study from England revealed a 3-fold increased risk to be associated with a low lifetime UV sunlight exposure (12). Results from our previous studies (23,24) have shown that outdoor UV sunlight exposure was associated with reduced PCa risk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, a case-control study from England revealed a 3-fold increased risk to be associated with a low lifetime UV sunlight exposure (12). Results from our previous studies (23,24) have shown that outdoor UV sunlight exposure was associated with reduced PCa risk.…”
Section: Discussionmentioning
confidence: 92%
“…However, Berndt et al did not find evidence to support an association between any of the VDR polymorphisms and the risk of PCa (33). We recently reported that VDR SNPs 4 (c907+75C>T) and 7 (rs7975232) play a significant role in the development of PCa in African Americans (7,23). The cumulative effects of VDR polymorphism, UV sunlight exposure, and vitamin D level on PCa risk has also been investigated by other researchers (34,35).…”
Section: Discussionmentioning
confidence: 96%
“…Different studies have examined the effect of IL-6 SNP and/or IL-8 SNP on diseases' risk, activity, and progression. Results showed marked ethnicity-associated disparities and diverse findings [12,[16][17][18][19][20][21][22][23]. For instance, a meta-analysis of European and Asian studies on IL-6 SNP and rheumatoid arthritis (RA) risk showed that IL-6 SNP was significantly associated with RA in Asian patients but not in the Caucasian population [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, three SNPs located near base excision repair genes were found to be negatively associated with Wilms tumor risk [32]. SNPs in the vitamin D receptor gene have also been linked to decreased risk in prostate cancer in African American men [33] and rs1866074 near the thymine DNA glycosylase gene were reported to be correlated with lower colorectal cancer risk [34]. The minor allele of rs112837127 is most prevalent in British and Finnish populations where the allele frequency could be > 5% while no African or east Asian population carries this allele [35].…”
Section: Discussionmentioning
confidence: 99%